Spoof surface plasmons tunneling through an epsilon-near-zero material channel. (24th August 2017) - Li, Zhuo; Sun, Yunhe; Sun, Hengyi; Wang, Kuan; Song, Jiajia; Liu, Liangliang; Chen, Xinlei; Gu, Changqing
Abstract: In this paper, squeezing and tunneling of spoof surface plasmon polaritons (SSPPs) are realized by introducing an effective epsilon-near-zero (ENZ) material channel between two plasmonic waveguides constructed from dielectric filled rectangular waveguide etched with deep sub-wavelength periodical transverse slots on the upper wall. The tunneling frequency can be flexibly tuned by changing the relative permittivity of the effective ENZ material and the SSPPs can tunnel efficiently through a straight or an arbitrarily bent effective ENZ channel with ultra-low loss. This simple design holds great promise in significantly increasing the propagation length or arbitrarily tuning the propagation direction of the SSPPs in the microwave and terahertz frequencies.